The human embryo and its right to live : a contribution to the sociology of death - Markešić, Ivan (Array, 2009)
The reasons for more discussion about the everyday promotion of such »culture of living« in western European society today can be found in the fact that between physicians, theologists, philosophers, ethicists and sociologists and others there is still no agreement on when human life truly begins. Actually, there is no unanimous opinion on whether human life begins with conception, or in some other phase of embryo development during pregnancy, or at birth. Because of this in different countries of the world different legal regulations exist on protection of human life, more specifically, in different countries different regulations exist on what timeframe is allowed for ending pregnancy without legal consequences.In the second part of this paper I would like to express the views of the current situation in Croatian society and state and highlight at least some controversy in the relationship between society and the embryo. In the Republic of Croatia, in which according to the latest census, almost 90% of citizens declared themselves Catholics, it is a legal right (by a decision of parliament representatives, mostly Catholic)